REDEFINITION OF POWER BY RAHIMA IN NADIA HASHIMI: “THE PEARL THAT BROKE ITS SHELL” - Amelia Febianingrum; Suci Suryani (Universitas 17 Agustus 1945 Surabaya, 2022)
Women as victims of sexist oppression is a global issue that needs attention from women around the world. This study covers three issues that relate to women as victims of sexist oppression. Those three issues are sexist oppression experienced by Rahima, solidarity gained by Rahima, and power exercised by Rahima in the novel entitled The Pearl That Broke Its Shell by Nadia Hashimi. Through qualitative methods, the researcher analyzes and describes character’s utterances and narrations from the narrator that indicate the existence of sexist oppression, women's solidarity, and women's power. The results showed that Rahima was successful in exercising her power to end the sexist oppression she experienced.